HIV is associated with endothelial activation despite ART, in a sub-Saharan African setting. Issue 2 (March 2019) - Kamtchum-Tatuene, Joseph; Mwandumba, Henry; Al-Bayati, Zaid; Flatley, Janet; Griffiths, Michael; Solomon, Tom; Benjamin, Laura
Abstract : Objective: To study the relationship between endothelial dysfunction, HIV infection, and stroke in Malawians. Methods: Using a cross-sectional design, we measured plasma levels of intercellular adhesion molecule-1 (ICAM-1), plasminogen activator inhibitor-1 (PAI-1), vascular endothelial growth factor (VEGF), and soluble thrombomodulin (sTM) in stroke patients and controls, stratified by HIV status. These biomarkers were measured using ELISA. After dichotomization, each biomarker was used as the dependent variable in a multivariable logistic regression model. Primary independent variables included HIV and stroke status. Adjustment variables were age, sex, hypertension, diabetes mellitus, tobacco and alcohol consumption, personal/family history of stroke, antiretroviral therapy status, and hypercholesterolemia. Results: Sixty-one stroke cases (19 HIV+) and 168 controls (32 HIV+) were enrolled. The median age was 55 years (38.5–65.0) for controls and 52 years (38.0–73.0) for cases ( p = 0.38). The median CD4 + T-cell count was 260.1 cells/mm 3 (156.3–363.9) and 452 cells/mm 3 (378.1–527.4) in HIV-infected cases and controls, respectively. HIV infection was independently associated with high levels of ICAM-1 (OR = 3.6, 95% CI: 1.3–10.6, p = 0.018) in controls but not in stroke cases even after excluding patients with a viral load >1, 000 RNA copies/mL (OR = 4.1, 95% CI: 1.3–13.1, p = 0.017). There was no association between the clinical profiles of HIV-positive controls or HIV-positive stroke and high levels of PAI-1, VEGF, and sTM. Conclusions: HIV infection is associated with endothelial activation despite antiretroviral treatment. Our findings underscore the need for larger clinical cohorts to better understand the contribution of this perturbation of the endothelial function to the increasing burden of cardiovascular diseases in sub-Saharan Africa.